Chelated lead and bone lead. - Tell, I.; Somervaille, L. J.; Nilsson, U.; Bensryd, I.; Schutz, A.; Chettle, D. R.; Scott, M. C.; Skerfving, Staffan (Scandinavian Journal of Work, Environment & Health, 1992)
In this study a close correlation [correlation coefficient (r) = 0.86, P less than 0.001] was found between the blood lead level of 20 lead workers and their urinary excretion of lead for 24 h after intravenous infusion with 1 g of the chelating agent calcium disodium edetate. In addition, there were significant associations between lead levels in different bones (tibia/calcaneus: r = 0.93, P less than 0.001; tibia/phalanx: r = 0.67, P less than 0.002; calcaneus/phalanx: r = 0.80, P less than 0.001), as measured by in vivo X-ray fluorescence. Chelation produced no significant change in the lead level in either tibia or calcaneus. There was a significant correlation between chelated lead and bone lead (eg, for calcaneus, r = 0.62) in currently exposed workers. However, there was no significant relationship when a retired worker and an inactive worker were included (r = 0.14). It was concluded that chelatable lead mainly reflects the blood and soft-tissue lead pool, which is only partly dependent upon the skeletal lead content that comprises the biggest share of the total body burden.